Analisis Nilai Dosis Radiasi yang diterima Rektum dan Kandung Kemih Pasien Kanker Serviks menggunakan Metode 2D dan 3D-CT pada Brakiterapi - Nurul Fathanah; Dian Milvita; Fiqi Diyona (Jurnal Fisika Unand, 2025)
Research has been conducted on the analysis of radiation doses received by the rectum and bladder of cervical cancer patients using 2D and 3D-CT methods in brachytherapy at the Radiation Oncology Installation of Andalas University Hospital. The study used data on cervical cancer patients stage IIB-IVA, as many as 10 patient data using the 2 Dimensional (2D) method and 10 patient data using the Three Dimensional Computed Tomography (3D-CT) method. Analysis was performed by comparing 2D and 3D-CT brachytherapy methods. The results showed that the average radiation dose value received by the rectum of patients using the 3D-CT method was 491.31 cGy and the 2D method was 466.13 cGy, while in the bladder the average radiation dose received by patients using the 3D-CT method was 448.39 and the 2D method was 480.30. The results showed that the average radiation dose using the 3D-CT method was greater than the 2D method, but the dose received by the rectum and bladder did not exceed the tolerance limit set by the American Brachytherapy society (ABS).